2015
DOI: 10.1111/jfb.12802
|View full text |Cite
|
Sign up to set email alerts
|

Retinal development in the gilthead seabream Sparus aurata

Abstract: The retinal development of the gilthead seabream Sparus aurata has been analysed from late embryonic development to juvenile stages using classical histological and immunohistological methods. Five significant phases were established. Phases 1 and 2 comprise the late embryonic and hatching stages, respectively. The results indicate that during these early stages the retina is composed of a single neuroblastic layer that consists of undifferentiated retinal progenitor cells. Phase 3 (late prolarval stage) is ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…55,[59][60][61][62] It has been demonstrated that the telomere dysfunction-induced senescence that occurs in the cells of mitotic tissues may limit the replicative potential of fibroblasts in the skin of monkeys, which would F I G U R E 6 SA-β-GAL activity, cell differentiation, and cell death in the HH36 G. gallus central retina. In more temporal/nasal regions, no vitreal staining was observed.…”
Section: Sa-β-gal Activity In the Nblmentioning
confidence: 99%
See 1 more Smart Citation
“…55,[59][60][61][62] It has been demonstrated that the telomere dysfunction-induced senescence that occurs in the cells of mitotic tissues may limit the replicative potential of fibroblasts in the skin of monkeys, which would F I G U R E 6 SA-β-GAL activity, cell differentiation, and cell death in the HH36 G. gallus central retina. In more temporal/nasal regions, no vitreal staining was observed.…”
Section: Sa-β-gal Activity In the Nblmentioning
confidence: 99%
“…The scleral labeling, which appeared as a continuous band located in the apical region of the neuroepithelial cells, coincided topographically with the mitotic activity that occurs in the differentiating vertebrate retina. 55,[59][60][61][62] It has been demonstrated that the telomere dysfunction-induced senescence that occurs in the cells of mitotic tissues may limit the replicative potential of fibroblasts in the skin of monkeys, which would F I G U R E 6 SA-β-GAL activity, cell differentiation, and cell death in the HH36 G. gallus central retina. Cryosections were doubly stained with SAβ-GAL histochemistry and antibodies against p21 (A-C), TUJ1 (D-F), and TUNEL histochemistry (I).…”
Section: Sa-β-gal Activity In the Nblmentioning
confidence: 99%
“…Due to the plasticity of M€ uller cells, they can be characterized by glial markers, cell cycle markers and stem cell markers (Roesch et al 2008). Among them, the enzyme glutamine synthetase (GS) has long been considered a good molecular marker for M€ uller glia in the developing and mature retinal tissue (Peterson et al 2001;Bejarano-Escobar et al 2009, 2012aPav on-Muñoz et al 2016). These cells also express selected classes of intermediate filament proteins, such as vimentin, glial fibrillary acidic protein (GFAP) and nestin (Raymond et al 2006;S anchez-Far ıas & Candal, 2016).…”
Section: Development and Function Of M€ Uller Gliamentioning
confidence: 99%
“…, , ; Pavón‐Muñoz et al. ). These cells also express selected classes of intermediate filament proteins, such as vimentin, glial fibrillary acidic protein (GFAP) and nestin (Raymond et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation